WORK-LIFE BALANCE: THE ROLE AND EFFORTS OF COMPANIES IN IMPROVING EMPLOYEE PERFORMANCE - Rio Mattajang (Sean Institute, 2023)
In an increasingly demanding work environment, balance between work and personal life has become an important aspect that can influence employee productivity and well-being. This research aims to examine the role of work-life balance and its efforts in improving employee performance. This research uses qualitative methods with descriptive methods. The research results show that the implementation of the work-life balance policy has a natural role in improving employee performance, namely by increasing productivity, providing better and happier mental health, increasing employee retention, strengthening the company's reputation and a more positive work environment. Apart from that, in the efforts we make towards employees in supporting the implementation of work-life balance in the work environment, there are several things that must be considered, namely providing realistic targets, setting a good example in terms of balance, holding collaborative events between employees and their families, and recognizing life. employees outside the company. Thus, implementing work-life balance is not only an organizational task, but also a shared responsibility to create a more humane and competitive work environment.